The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.amepre.2012.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Financial Outlays for Purchasing Alcohol Brands in the U.S.

Abstract: Background Low alcohol prices are a potent risk factor for excessive drinking, underage drinking, and adverse alcohol-attributable outcomes. Presently, there is little reported information on alcohol prices in the U.S., in particular as it relates to the costs of potentially beneficial amounts of alcohol. Purpose To determine the minimum financial outlay necessary to purchase individual brands of alcohol using online alcohol price data from January through March 2012. Methods The smallest container size an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Moreover, we found that percent of alcohol by volume varied greatly between brands within each beverage category (DiLoreto et al, 2012). Because of these variations in alcohol content and price, 21 of the 25 least expensive alcohol brands were priced at less than $1.00 per standard drink (Albers et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we found that percent of alcohol by volume varied greatly between brands within each beverage category (DiLoreto et al, 2012). Because of these variations in alcohol content and price, 21 of the 25 least expensive alcohol brands were priced at less than $1.00 per standard drink (Albers et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the availability of smaller container sizes that require a lower outlay of money may increase the appeal of that brand to underage drinkers who tend to have less spending money. Hence, for each brand, we determined its minimum container size and the minimum financial outlay required to purchase that particular product during the period January-March 2012 (65). Using these figures, we estimated the number of standard drinks of each brand that could be purchased for five dollars and used this as an additional control variable.…”
Section: Methodsmentioning
confidence: 99%
“…There are, of course, additional factors to be considered apart from the potential influence of alcohol marketing, including differential brand availability by geographic region, parental and peer alcohol brand preferences, retail pricing, and beverage flavor/taste. We have published analyses of alcohol price data and youth versus adult alcohol preferences elsewhere (DiLoreto et al, 2012;Albers et al, 2013;Siegel et al, 2013bSiegel et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%